2011
DOI: 10.1097/ccm.0b013e3182227a27
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive versus invasive ventilation for acute respiratory failure in patients with hematologic malignancies: A 5-year multicenter observational survey*

Abstract: In patients with hematologic malignancies, acute respiratory failure should probably be managed initially with noninvasive mechanical ventilation. Further study is needed to determine whether immediate invasive mechanical ventilation might offer some benefits for those with acute lung injury/adult respiratory distress syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
98
1
15

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 190 publications
(121 citation statements)
references
References 35 publications
7
98
1
15
Order By: Relevance
“…[60][61][62]. A large observational multicentre Italian survey investigated the clinical impact of NIV use in 1302 haematological patients admitted to the ICU with ARF [63]. The authors, after a propensity score analysis, confirmed the role of NIV as an independent predictor of survival.…”
Section: Recommendationmentioning
confidence: 73%
“…[60][61][62]. A large observational multicentre Italian survey investigated the clinical impact of NIV use in 1302 haematological patients admitted to the ICU with ARF [63]. The authors, after a propensity score analysis, confirmed the role of NIV as an independent predictor of survival.…”
Section: Recommendationmentioning
confidence: 73%
“…Most observational studies and subgroup analyses of RCT show that patients with acute respiratory distress syndrome (ARDS) are among those with the worst outcome when they receive NIV as a support measure for severe hypoxemic ARF, with high rates of NIV failure (28,30,(35)(36)(37)(38), and limited efficacy of NIV. The severity of arterial hypoxemia and the frequent impairment of pulmonary mechanics in these patients may explain the high intubation rate showed in several studies, regardless of NIV use or not.…”
Section: Acute Respiratory Distress Syndromementioning
confidence: 99%
“…4.478 cies who are admitted to an intensive care unit (ICU) for respiratory support, half will require mechanical ventilation [9]. However, the need for mechanical ventilation in patients with hematologic malignancies is associated with a poor prognosis [10,11].…”
Section: Introductionmentioning
confidence: 99%